Venous thromboembolism after fast-track elective revision hip and knee arthroplasty – A multicentre cohort study of 2814 unselected consecutive procedures. Issue 199 (March 2021) - Petersen, Pelle Baggesgaard; Lindberg-Larsen, Martin; Jørgensen, Christoffer Calov; Kehlet, Henrik; ,; Madsen, Frank; Hansen, Torben B.; Gromov, Kirill; Kjærsgaard-Andersen, Per; Solgaard, Soren; Bagger, Jens
Abstract: Background: Venous thromboembolism (VTE) prophylaxis is much debated within total hip and knee arthroplasty (THA/TKA). Revision hip and knee arthroplasty (rTHA/rTKA) are more extensive procedures, but data on the risk of postoperative VTE is conflicting and there are no specific guidelines for thromboprophylaxis. Furthermore, data on rTHA/rTKA within a fast-track protocol is sparse. Thus, we aimed at evaluating the incidence and time course of VTE in unselected elective rTHA/rTKA within our established multicentre fast-track collaboration with in-hospital only thromboprophylaxis if length of stay (LOS) ≤ 5 days. Methods: We used an observational study design of unselected consecutive fast-track elective major component rTHA/rTKA from 6 dedicated fast-track centres between 2010 and 2018. We obtained information on revisions through Danish hip and knee arthroplasty registers and complete (>99%) 90 days follow-up through the Danish National Patient Registry in combination with chart review. Results: We included 2814 procedures with median LOS 3 days [2–5] and 21% had LOS >5 days. The 90-day incidence of VTE was 0.42% (n = 12), with 8 (0.28%) DVT and 4 (0.14%) PE, after median 14 days [IQR: 11–23] with the latest on day 31. Conclusion: The 90-day incidence of VTE after elective fast-track rTHA and rTKA was about 0.4% which is comparable to the 90-day VTE incidence after primary fast-track THA, TKA and unicompartmental knee arthroplasty. Future investigations should focus on identification of high-risk patients while the surgical trauma per se may be less important. Highlights: Postoperative VTE after elective fast-track revision hip and knee arthroplasty is largely uninvestigated. We found a 90-day VTE incidence of 0.42%, 0.36% after rTKA and 0.54% after rTHA. The VTE incidence was similar to reports on fast-track THA/TKA and UKA from the same centres. The VTE's occurred after median 14 days. We found no cases of 90-day VTE related mortality.